ANALISIS PENGARUH UKURAN, UMUR UMKM DAN KETERAMPILAN MANAJEMEN KEUANGAN TERHADAP SISTEM AKUNTANSI FORMAL USAHA MIKRO KECIL DAN MEMENGAH (UMKM) DI KABUPATEN BREBES - Kurniawan Kurniawan; Anies Indah Haryanti (Monex: Journal of Accounting Research, 2016)
In practice SMEs in Indonesia has always faced serious problems, either on the operating conditions and specific characteristics of SMEs. The failure of SME’s usually caused by some factors, such as: from the manger, the owner that have some of the functions of accountability, and financial manager, or one of them. The purpose of this study was to determine the effect of age, size and financial management skills to the formal accounting system of SMEs in Brebes.The results showed that there were significant age, size and financial management skills to the formal accounting systems of SMEs in Brebes. The results could have implications for SMEs to prepare formal accounting system availability, otherwise it will provide relevant and accurate information about the financial condition of companies that can be used as a basis for decision making, the information is also useful in the availability of credit access to financial institutions.Keywords: formal accounting system, financial management skills, SMEs